Assessment of equine intestinal epithelial junctional complexes and barrier permeability using a monolayer culture system - Stewart, Amy Stieler; Kopper, Jamie J.; McKinney-Aguirre, Caroline; Veerasamy, Brittany; Sahoo, Dipak Kumar; Freund, John M.; Gonzalez, Liara M. (Frontiers in Veterinary Science, 2024)
Gastrointestinal disease is a leading cause of death in mature horses. A lack of in vitro modeling has impeded the development of novel therapeutics. The objectives of this study were to develop and further characterize a small intestinal monolayer cell culture derived from equine jejunum including establishing normal measurements of intestinal permeability and restitution. Three-dimensional enteroids, derived from postmortem sampling of equine jejunum, were utilized to develop confluent epithelial monolayers. The presence of differentiated intestinal epithelial cell types and tight junctions were confirmed using histology, reverse transcription PCR (RT-PCR), RNAscope, protein immunofluorescence and transmission electron microscopy. Transepithelial resistance (TER) and macromolecule flux were assessed as measurements of paracellular and transcellular permeability. Scratch assays were utilized to model and assess intestinal restitution. Monolayer cell cultures reached 100% confluency by ~5–7 days. Equine jejunum monolayers were confirmed as epithelial in origin, with identification of differentiated intestinal epithelial cell types and evidence of tight junction proteins. Function of the intestinal barrier was supported by acquisition of physiologically normal TER values (179.9 ± 33.7 ohms*cm2) and limited macromolecule flux (22 ± 8.8% at 60 min). Additionally, following a scratch wound, epithelial cell monolayers migrated to close gap defects within 24 h. In conclusion, this study describes the development of a novel intestinal epithelial monolayer cell culture for equine jejunum, and provides evidence of intestinal epithelial cell differentiation, formation of physiologically relevant barrier function and use as a model of intestinal restitution to test potential therapeutics for equine colic.